2020
DOI: 10.1002/gj.3915
|View full text |Cite
|
Sign up to set email alerts
|

Clay mineral diagenesis and red bed colouration: A SEM study of the Gercus Formation (Middle Eocene), northern Iraq

Abstract: Detailed high magnification scanning electron microscopic (SEM) study supported by petrographic, mineralogical, and geochemical (major and trace element) analysis of the Gercus Formation clastics (sandstones and mudstones) from northern Iraq shows that the main authigenic components are carbonate (dolomite and calcite), clay and haematite minerals with rare quartz, feldspar, and gypsum. The carbonates and sulphate minerals were the main early diagenetic phase in the Gercus Formation and were produced from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 63 publications
(119 reference statements)
0
4
0
Order By: Relevance
“…However, kaolinite is more likely to be inherited from kaolinitic source, since detrital kaolinite is very unlikely to form in seawater [25]. Previous studies confirmed the presence of kaolinite in the river environments (Gercus) [26], which is established in these continental environments due to the presence of acid solutions that have a suitable environment for sedimentation [1]. Detrital origin of kaolinite relates mostly to derivation from igneous rocks that are rich in potash feldspars or from reworking of older sedimentary rocks [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, kaolinite is more likely to be inherited from kaolinitic source, since detrital kaolinite is very unlikely to form in seawater [25]. Previous studies confirmed the presence of kaolinite in the river environments (Gercus) [26], which is established in these continental environments due to the presence of acid solutions that have a suitable environment for sedimentation [1]. Detrital origin of kaolinite relates mostly to derivation from igneous rocks that are rich in potash feldspars or from reworking of older sedimentary rocks [27].…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 6) is notably different from the other formations. Oxidizing depositional conditions are widely used to explain the coloration of red sandstones in the Yili Basin [73,74] and elsewhere [75]. These sedimentary features are supported by the Mo EF values to imply that the sediments in the Sangonghe Fm.…”
Section: Redox Conditionmentioning
confidence: 91%
“…Most of the hematite is in tiny crystal agglomerates or in individual microcrystals form in the pores of the montmorillonite and exhibit a variety of shapes (Figure 2d) [47]. There are spherical, rod-shaped, leaf-shaped, and well-developed hexagonal flake hematite single crystals, as well as fibrous to lath-shaped, rosette clusters and spherical hematite/goethite aggregates (Figure 2c-f) [47,48]. These morphological features are closely related to the relative abundance of the iron-bearing mineral precursors in the rocks.…”
Section: Distribution and Existence Of Hematitementioning
confidence: 99%
“…Compared with the hematite in the form of single or polycrystalline aggregates, the latter (mixed with clay minerals) is more widely distributed in time and space, appearing in red beds of all ages. In Mesozoic and Cenozoic red beds, hematite is almost only adsorbed on the surface and/or in the voids of clay minerals [41,48,50]. In older red beds, hematite can be depleted to varying degrees due to later tectonics, groundwater penetration, or the participation of hydrothermal fluids, and then replaced by euhedral to semi-hedral authigenic hematite grains formed in situ and secondary pores or aggregates [42,43].…”
Section: Distribution and Existence Of Hematitementioning
confidence: 99%